Market and Freedom - Stoilova, Vyara (Research Papers, 2024)
The article focuses on freedom as one of the core values of the market institution. The purpose of the analysis is to conceptualize the freedom of the market actor to pursue his own interest as an organic part of the human life strategy. A special place is devoted to the relationship between money and freedom, which is structural for the role ensemble of the person and which in certain cases leads to social exclusion. The proposed analysis can serve to develop a theoretical model for the empirical study of the subjective evaluations of the freedom that the institution of the market provides to the person to realize his life strategy.